The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cam4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Global circular RNA expression profile of human gastric cancer and its clinical significance

Abstract: Circular RNAs (circRNAs) are a new class of noncoding RNAs. However, the expression profile and clinical significance of circRNAs in human gastric cancer is unclear. The global circRNA expression profile in human gastric cancer was measured by circRNA microarray. Hsa_circ_0014717, one of the most downregulated circRNAs in microarray, was selected as a targeted circRNA to explore its levels in gastric tissues and gastric juice. Freeze-thaw experiment and incubation experiment confirmed the stability of gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
210
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 223 publications
(221 citation statements)
references
References 24 publications
7
210
2
2
Order By: Relevance
“…It was demonstrated that circRNAs are involved in the development of several types of diseases, such as atherosclerosis, myocardial Infarction and neuron injury [10][11][12]. Indeed, there has been a special outpouring of concern for immense amounts of research shown that circRNAs are associated with many human cancers, such as hepatocellular carcinoma [13], esophageal squamous cell carcinoma [14], human gastric cancer [15], colorectal cancer [16]. Our previous study showed that circRNA alterations are involved in resistance to avian leucosis virus subgroup-J-induced tumor formation in chickens [17], however, no reports showed that circRNAs play a key role in chicken cancer which was induced by avian leucosis virus subgroup-J (ALV-J).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that circRNAs are involved in the development of several types of diseases, such as atherosclerosis, myocardial Infarction and neuron injury [10][11][12]. Indeed, there has been a special outpouring of concern for immense amounts of research shown that circRNAs are associated with many human cancers, such as hepatocellular carcinoma [13], esophageal squamous cell carcinoma [14], human gastric cancer [15], colorectal cancer [16]. Our previous study showed that circRNA alterations are involved in resistance to avian leucosis virus subgroup-J-induced tumor formation in chickens [17], however, no reports showed that circRNAs play a key role in chicken cancer which was induced by avian leucosis virus subgroup-J (ALV-J).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are widely detected in blood, saliva and body fluid, and their abundance is higher compared with linear RNAs 53 54. Besides, it was reported that circRNA was extremely stable and frequent freeze–thaw does not affect its biological property 55. Recently, studies have indicated that the superiority of circRNAs as prognosis biomarker could reflect the stage characteristics of tumourigenesis 39 48.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with paired adjacent non-tumorous tissues, hsa_circ_0003159 expression was significantly down-regulated in gastric cancer tissues and significantly negatively associated with gender, distal metastasis, and tumor-node-metastasis stage [34]. Similarly, hsa_circ_0014717 was significantly down regulated as well in gastric cancer tissues and related to tumor stage, distal metastasis, tissue carcinoembryonic antigen and carbohydrate antigen 19-9 expression [35]. However, some circRNAs are upregulated in GC tissues and play a vital role in promoting the development of gastric cancer.…”
Section: Correlation Of Circrnas To Gastric Cancermentioning
confidence: 91%